Analytic solution of transcendental equations - Górecki, Henryk (1927-2022) (Zielona Góra: Uniwersytet Zielonogórski)
A decomposition technique of the solution of an n-th order linear differential equation into a set of solutions of 2-nd order linear differential equations is presented.
Keywords: transcendental equations; zeros; extrema